PERAN INTERNATIONAL ORGANIZATION FOR MIGRATION DALAM KASUS WOMEN TRAFFICKING ASAL UKRAINA DI JERMAN TAHUN 2008-2012 - Ningsih, Rini Oktiwi; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This paper described the role of International Organization for Migration in preventing women trafficking cases from Ukraine to Germany. These women were sent illegaly to German area in which then they became sex workers.The theory that has been employed in this paper was the role theory based on Walker in which enables to explain a symbolic value not only for individual but also groups. Unit analysis that has been used was international organization with security human consept in which this concept was targeted to analysis traditional security.The result of this paper has proved that IOM signed Memorandum of Understanding Cooperation with Ukraine Government which purpose for consolidating to improve Ukraine legislation especially in war against human trafficking.